Instrument to determine the predictors of innovation capacities in the context of health organizations. Assessment of your reliability [Instrumento para determinar los predictores de las capacidades de innovación en el contexto de las organizaciones de salud. Evaluación de su confiabilidad] (2018)
The purpose of this proposal is to test the reliability of an instrument in the context of health care organizations. Three techniques were applied to a pilot sample of 108 observations: 1) the test of the two halves, where they are correlated, in order to obtain the reliability coefficient for each one, and Spearman-Brown is used to infer such reliability of the complete test; 2) the internal consistency test yielded an average indicator of 0.94; and 3) The correlation-item-total test yielded very high correlations and levels of significance < 0.05 for each predictor of innovation capability. © 2018.